Increased AMPA receptor GluR1 subunit incorporation in rat hippocampal CA1 synapses during benzodiazepine withdrawal - Das, Paromita (2008)
Prolonged benzodiazepine treatment leads to tolerance and increases the risk of dependence. Flurazepam (FZP) withdrawal is associated with increased anxiety correlated with increased AMPAR-mediated synaptic function and AMPAR binding in CA1 pyramidal neurons. Enhanced AMPAR synaptic strength is also associated with a shift toward inward rectification of synaptic currents and increased expression of GluR1, but not GluR2 subunits, suggesting augmented membrane incorporation of GluR1-containing, GluR2-lacking AMPARs. To test this hypothesis, the postsynaptic incorporation of GluR1 and GluR2 subunits in CA1 neurons after FZP withdrawal was examined using postembedding immunogold quantitative electron microscopy. The percentage of GluR1 positively-labeled stratum radiatum (SR) synapses was significantly increased in FZP-withdrawn rats (88.2 ± 2.2%) compared to controls (74.4 ± 1.9%). In addition, GluR1 immunogold density was significantly increased by 30% in SR synapses in CA1 neurons from FZP-withdrawn rats compared to control rats (FZP: 14.1 ± 0.3 gold particles/μm; CON: 10.8 ± 0.4 gold particles/μm). In contrast, GluR2 immunogold density was not significantly different between groups. Taken together with recent functional data from our laboratory, the current study suggests that the enhanced glutamatergic strength at CA1 neuron synapses during benzodiazepine withdrawal is mediated by increased incorporation of GluR1-containing AMPARs. Mechanisms underlying synaptic plasticity in this model of drug dependence are therefore fundamentally similar to those that operate during activity-dependent plasticity.